Composition, mineralization potential and release risk of nitrogen in the sediments of Keluke Lake, a Tibetan Plateau freshwater lake in China. Issue 9 (26th September 2018) - Wang, W. W.; Jiang, X.; Zheng, B. H.; Chen, J. Y.; Zhao, L.; Zhang, B.; Wang, S. H.
Abstract : The lakes distributed in the Tibetan Plateau constitute a lake group with the highest altitude, largest lakes and largest area in the world and are important in global climate and environmental effects. Freshwater lakes in the Tibetan Plateau possess high ecological values and high vulnerability. The migration and transformation of nitrogen in sediments are critical to lake ecosystems, but information on sedimentary nitrogen in the freshwater lakes in the Tibetan Plateau is limited. A case study was conducted in Keluke Lake, China, to reveal the effects of sedimentary nitrogen on water quality in plateau freshwater lakes. Nitrogen speciation, mineralization potential and release flux were analysed through a sequential extraction method, waterlogged incubation experiment and Fick's first diffusion law, respectively. The content of total nitrogen (TN) was 1295.75–6151.69 mg kg −1, and 94.2% of TN was organic nitrogen (ON). The contents of three nitrogen fractions were in the order of hydrolysable nitrogen > residual nitrogen > exchangeable nitrogen. Ammonia nitrogen ( N H 4 + − N ) was the main mineralization product, and hydrolysable ON was the most significant contributor. The sediments showed a great mineralization potential, with a potentially mineralizable nitrogen value of 408.76 mg N kg −1 of sediment, that was mainly affected by hydrolysable ammonium nitrogen. The N H 4 + − N diffusion flux ranged from 24.14 to 148.75 mg m −2 d −1, and the sediments served as an internal nitrogen source. Nitrogen release from sediments was considerably influenced by exchangeable ammonia nitrogen. The sediments in Keluke Lake pose a potential nitrogen release risk and threaten the water quality of the lake. The total content, speciation, mineralization of ON and the release flux at sediment–water interface should be considered comprehensively to evaluate the effects of nitrogen in sediments to water quality.